DETERMINANTS OF ECONOMIC GROWTH IN THE OIC COUNTRIES: A GMM MODEL - Lusiana, Dewi; Wau, Taosige; Wibowo, Muhammad Ghafur; Choiri, Miftakhul; Salic, Jawad Z. (Universitas Airlangga, 2025)
Development issues are central to countries across the world, regardless of whether they are classified as developed or developing. The success or failure of development efforts is often reflected in the level of a nation’s economic growth, as this indicator serves as a key benchmark for assessing overall economic progress. Therefore, this study aims to have investigated how foreign direct investment (FDI), human capital, trade openness, and corruption influence the economic growth of OIC countries over the period 2012–2023. The analysis employs a dynamic panel framework using the Generalized Method of Moments (GMM). This study found that FDI has a negative and substantial influence on economic growth, that reveals the existence of obstacles to the utilization of foreign investment in the OIC region. In contrast, human capital and trade openness exert to have a favorable and substantial impact on economic growth, whereas corruption reveals to have a negative and substantial influence. The primary contribution of this research lies to having integrated corruption as a key determinant, an aspect that has received to have relatively limited attention in earlier studies on economic growth. Therefore, the policy implications of these outcomes emphasize the importance of implementing structural reforms to improve to have anti-corruption governance and create to have a trade and political environment that supports to have the acceleration of sustainable economic growth in OIC countries.